Karakteristik Perilaku Informasi Pustakawan Universitas Pembangunan Panca Budi (UNPAB) Dalam Menelusuri Informasi - Purwaningtyas, Franindya; Maruhawa, Illiyyin Hanifah; Pangestu, Mirawati Idi; Ramadhan, Ratih; Mulanda, Wida (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to examine the behavioral characteristics of information tracing by librarians at the Library of the Panca Budi Development University (UNPAB) Medan. This study uses Lekkie's perspective as one of the theories that addresses the behavioral model of information tracing. Leskie's theory in information tracing focuses on professionals, and librarians are professions in the field of library and information science. The method used is a qualitative method with a technique of taking through structured interviews with UNPAB Librarians and observations of the UNPAB Library. In addition, literature study techniques were used in the process of this study. The result of this study is a librarian in carrying out roles and work duties as a mediator and educator. Librarian as a mediator, meaning Librarian helps users get the information they need. UNPAB librarians assist and direct users regarding the need for references to scientific papers. Librarians as educators, namely librarians provide teaching such as user education which is routinely carried out by UNPAB Librarians. Through the user education program, users are given knowledge about the UNPAB library from its profile to the services available in the UNPAB Library. UNPAB librarians search for information from a variety of sources. For example, to search for secondary sources of information using online catalogs (OPAC) and for scientific reference, they use repositories or in the search for sources of information in the form of scientific reports referring to repositories and databases of scientific journals. Then, the final stage is the result of searching for information. If successful, it will feel satisfaction for the information searcher and vice versa if it is not satisfactory, then carry out the tracing process from the initial stage. Keywords: Information Behavior, University Librarian, Leckie Theory.